Apoyo a la supervisión de obra del proyecto construcción civil metálica de viviendas unificadas en el Municipio de Villa de Leyva (2022)
At present, the construction of three unified houses is being carried out, having a total area of 500 m2 with the culmination of 3 elements such as: metal, glass, ecological materials (pressed adobe brick), reuse of water and the use of solar panels. This Document shows each of the processes carried out and each of the activities that the intern carried out, providing support in the execution of the project in the municipality of Villa de Leyva, fully complying with what was proposed and constantly monitoring and controlling the previous construction progress.